Slow Potentials in Time Estimation: The Role of Temporal Accumulation and Habituation - Kononowicz, Tadeusz W.; Van Rijn, Hedderik (Frontiers in Integrative Neuroscience, 2011)
Numerous studies have shown that contingent negative variation (CNV) measured at fronto-central and parietal-central areas is closely related to interval timing. However, the exact nature of the relation between CNV and the underlying timing mechanisms is still a topic of discussion. On the one hand, it has been proposed that the CNV measured at supplementary motor area (SMA) is a direct reflection of the unfolding of time since a perceived onset, whereas other work has suggested that the increased amplitude reflects decision processes involved in interval timing. Strong evidence for the first view has been reported by Macar, Vidal and Casini (1999), who showed that variations in temporal performance were reflected in the measured CNV amplitude. If the CNV measured at SMA is a direct function of the passing of time, habituation effects are not expected. Here we report two replication studies, which both failed to replicate the expected performance-dependent variations. Even more powerful linear-mixed effect analyses failed to find any performance related effects on the CNV amplitude, whereas habituation effects were found. These studies therefore suggest that the CNV amplitude does not directly reflect the unfolding of time